Textual Metafunction Analysis in Surah Maryam and The Gospel of Luke: A Comparative Analysis - Putri, Anabel Dwiana; Rosita, Nur (Universitas Negeri Padang, 2023)
This study aims to analyze and compare the Textual Metafunction in Surah Maryam and The Gospel of Luke. The texts were analyzed using Halliday and Matthiesen’s type of Themes theory and Danes’ thematic progression theory. There are three types of themes, namely topical, interpersonal, and textual themes. Also, there are three types of thematic progression, which are simple linear, constant continuous, and derived hyper-theme progression. While the data from this research is in the form of text. This study focused on comparing the theme types and thematic progression found in both texts. In analysis, both of the texts are mostly using an unmarked topical theme which aims to make the information conveyed in the text clear and easily understood by the reader. For the thematic progression, both of the texts also mainly use derived hyper-theme progression which focuses on a single Theme.